Os caminhos e os descaminhos da ciência na obra de Ernesto Sabato - Hülsendeger, Margarete Jesusa Varela Centeno (2020)
Scientific and literary creation are founded on a perception that often overcomes the barrier of factual reality, becoming a desire to know and to be known, regardless of the methodology employed. When writers write inspired by science and scientists write novels, it possible to see an attempt to overcome this gap between literati and scientists. However, in the case of the argentine writer Ernesto Sabato (1911-2011), in can be noticed the opposite, since his essays often find a radical stance against scientific thinking and technological advances. This position allowed the following question: is this "aversion" to everything that concerns science materialized in his novels? In this sense, the central hypothesis of this thesis is that in the three literary works of Ernesto Sabato – The tunnel (1948), On heroes and tombs (1961) and The angel of darkness (1974) – can be found elements or ideas that point to a rejection of scientific thinking, which often appears in essays. To identify and characterize these elements, the methodology used was content analysis and the corpus was constituted, not only of the three novels already mentioned, but also of nine essayistic works: Uno y el universo (1945), Hombres y engranajes (1951), Heterodoxia (1953), El escritor y sus fantasmas (1963), Tango discusión y clave (1963) y Tres aproximaciones a la literatura de nuestro tiempo (1968), Apologías y rechazos (1979), Antes del fin (1998) y La resistencia (2000). Thus, in the analysis of the “sabatianos” essays a rejection of the foundations of modern science - abstraction, rigor, logic, neutrality - was perceived, with the author holding them responsible for the crisis in which contemporary man finds himself. However, when the subject is literature there is a need to reaffirm that only it would be able to rescue man from this dark structure of modern times. These antagonistic points of view appear in the choice of the works and authors that formed his literary canon – Fiódor Dostoievski, Paul Valéry, Edgar Allan Poe, Jean-Paul Sartre and Jorge Luis Borges – praising and criticizing them according to the positions they adopted when the subject was science. In the novels, his conceptions of science are present mainly in the way he builds his characters, because in creating paranoid individuals (Juan Pablo Castel and Fernando Vidal Olmos) he highlights all those characteristics associated with scientific thought, demonstrating his repulsion to this point of view that values the abstraction, logic and impartiality over the human spirit. However, by creating characters involved with the writing process (Bruno, “Sabato”, “S”) he not only wants to communicate his concept of literature, but also to expose its role in a world that, according to him, is dominated by scientific abstractions. Thus, it was possible to demonstrate that the aversion to science exposed by Ernesto Sabato, in his essays, is materialized in the construction of his novels, especially in the discourse of his characters. However, it was also possible to observe that this aversion, repeatedly expressed by the author, became, even if against his will, literary material.